Improved bioactivity and composition of Cordyceps militaris cultured with Panax ginseng - LI,Li (2021)
Abstract Cordyceps militaris is a commonly used edible and medicinal fungus in East Asia. Preparation of the mycelium and fermentation liquid by submerged fermentation using additives such as Panax ginseng for skin whitening applications has attracted wide attention. In the present study, we screened traditional Chinese medicines as additives to the liquid fermentation medium for C. militaris and performed systematical research on the changes of bioactivity and ginsenoside levels during the fermentation process. Total polysaccharide contents, cordycepin content, and polysaccharide molecular weight in the fermentation products were measured by UV spectrophotometry, high-performance liquid chromatography-diode array detection (HPLC/DAD), and gel permeation chromatography-multi angle laser light scattering (GPC-MALLS), respectively. In addition, the ginsenosides Rb1, Re, Rd, Rg1, and pseudoginsenoside F11 in the fermentation products were quantitatively analyzed by ultra-performance liquid chromatography/tandem mass spectrometry (UPLC/MS/MS). Panax ginseng significantly increased the cordycepin and total sugar contents, and the average molecular weight of polysaccharides in the fermentation liquid and the mycelium of C. militaris. At the same time, C. militaris enhanced the production of ginsenoside pseudoginsenoside F11, which is a unique component of Panax quinquefolium. The research provides scientific evidence for the application of C. militaris and P. ginseng as raw materials for food and medicines.